Great Enhancement of Self‐Powered Photoresponse Performance of C3H8NSi‐TiO2 NRAs/n‐Si Heterojunction by Build‐In and Build‐Out Electric Field Jointly Promoting Carrier Separation. (19th July 2020) - Hou, Zhidong; Li, Guixia; Ling, Cuicui; Wang, Hongyan; Zhu, Lei; Guo, Tianchao; Zhang, Tuo; Feng, Bingxin; Cao, Min; Xue, Qingzhong
Abstract: A novel silane coupling agent grafting TiO2 nanorod arrays (C3 H8 NSi‐TiO2 NRAs)/n‐Si heterojunction is introduced. A built‐out electric field is created on the surface of TiO2 NRAs by silane coupling agent modifications, which can promote photo‐generated carriers separation so that the C3 H8 NSi‐TiO2 NRAs/n‐Si heterojunction shows excellent self‐powered broadband photoresponse properties. Especially under 900 nm illumination, the self‐powered device demonstrates the responsivity ( R ), detectivity ( D* ), and sensitivity ( S ) of ≈7.76 A W −1, ≈5.22 × 10 14 Jones, and ≈1.12 × 10 10 cm 2 W −1, respectively. Compared with that of the unmodified TiO2 NRAs/n‐Si heterojunction, the R, D*, and S are increased by two orders of magnitude. The results are mainly ascribed to the original built‐in electric field of heterojunction and the created built‐out electric field which jointly promote carriers separation and the unconventional porous electrode which plays a crucial role in collecting holes. The DFT calculations and TRPL results indicate the formation and carriers separation capability of the built‐out electric field. This design concept can be extended to the application of other varieties of metal oxide based photoelectric devices. Abstract : The outstanding self‐powered photoresponse performance of C3 H8 NSi‐TiO2 NRAs/n‐Si heterojunction can be attributed to the build‐in and build‐out electric field jointly promoting carriers separation. After modifications, the R, D*, and S are increased by two orders of magnitude. These results make self‐powered PDs promising for device applications that require high responsivity, excellent photosensitivity, and stability.